Analisis Teknik Penerjemahan Dalam Film Horror Incantation - Simbolon, Elisabeth Mahalito; Adha , T. Kasa Rullah (Riviera Publishing, 2025)
This study aims to find out how translators use translation techniques and what factors cause the use of translation techniques to appear, especially in subtitles. The type of research used in this study is descriptive qualitative research. The data has been collected by using listening and note-taking techniques. Based on the analysis of 18 data in the form of horror utterances in Incantation movie, it is found that there are 6 types of translation techniques used in the 18 data, starting from adaptation translation techniques with 7 data. There are 6 types of translation techniques applied in the translation of Incantation film subtitles, starting from adaptation translation techniques with 7 data. Second, there is a literal translation technique with 5 data. The third is a modulation technique with 4 data. Fourth, there are borrowing and linguistic compression techniques with 3 data. And the last one, there is a transposition technique with 1 data.